Historia Zakładu i Katedry Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego 1960–2014 - Mackiewicz, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The history of research and teaching on the history of political and legal doctrines at the Faculty of Law, Administration and Economics of the University of Wrocław dates back to 1946. In 1960, Franciszek Ryszka together with Jan Baszkiewicz started organizing the future Department of Political and Legal Doctrines Katedra Doktryn Polityczno-Prawnych at the Faculty of Law at Wrocław University. At that time, the historical and legal current of the German studies began to develop at the Faculty of Law. That current, represented by F. Ryszka, K. Jonca, A. Konieczny and F. Połomski, included research on such issues as the state and the law of the Third Reich, the functioning of the Nazi authorities, the history of the Jewish people and the issue of “Endlӧsung”. The Division of the History of Political and Legal Doctrines Zakład Historii Doktryn Politycznych i Prawnych, established in 1969 under the direction of Karol Jonca, started a new chapter in Polish studies on the German political and legal thought, especially political parties and movements in the Wilhelmian Empire, the Weimar Republic, the Third Reich, during the Second World War, and also in the post-war Germany. The Wrocław Department of the History of Political and Legal Doctrines soon became a leading research center specializing in the studies on the issues of fascism and Nazism. The establishment of the scientific journal entitled Studia nad Faszyzmem i Zbrodniami Hitlerowskimi [Studies on Fascism and Nazi Crimes] was the culmination of the developing of a research center. The first issue of the Studies, published as part of the Acta Universitatis Vratislaviensis series, appeared in 1974. The journal later transformed into one of the most important titles in which all of the major experts on the issues of Nazi crimes and the theory and forms of totalitarianism from Poland, Germany, the United Kingdom, France, Canada, and Ukraine, published their works. The Department of Political and Legal Doctrines Katedra Doktryn Politycznych i Prawnych has been headed by Professor Marek Maciejewski since 2001. Under his chairmanship, the members of the Department still pursue research on totalitarianism and authoritarianism, and conduct research on these currents of the political and legal thought which have the greatest impact on the contemporary social and political life. Among the issues of a special interest we must list liberalism, conservatism, the Catholic social teaching, Islamism, anarchism, the Polish political and legal thought in the Second Republic, and the idea of the European integration, both in historical and contemporary approach.
Keywords: Zakład i Katedra Doktryn Politycznych i Prawnych; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia